Intellectual Property Law in the Age of Artificial Intelligence: Legal Challenges and Regulatory Perspectives - Popov, Viktor; Popova, Sofiia; Zlakoman, Ihor; Kolomiiets, Serhii; Petrova, Nataliia (NAJAHA, 2025)
The study's relevance is stipulated by the rapid development of artificial intelligence (AI) and the need to adapt legal regulation in intellectual property to modern technological challenges. The absence of a unified approach to determining authorship and protecting rights to objects created by AI creates legal uncertainty and hinders innovation development. The study aims to analyse the existing approaches to regulating intellectual property rights created by AI and develop recommendations for improving the legislation. The object of the study is the legal acts and doctrinal approaches to the regulation of rights to the results of AI activities. This research uses a multidisciplinary approach by combining comparative legal methods, content analysis, historical, structural-system, forecasting, and empirical analysis. This approach allows for an in-depth analysis of intellectual property regulations in the context of artificial intelligence in various jurisdictions and the preparation of data-based policy recommendations and future projections. The study results showed a significant fragmentation of AI regulation in different jurisdictions. It analyses the models used in the USA, EU, China, UK, and other countries, identifying their strengths and weaknesses. Recommendations on harmonizing international standards and adapting the Berne Convention and the TRIPS Agreement to modern technological conditions are proposed. The practical significance of the work is to form the basis for the development of universal legal mechanisms that will help protect intellectual property rights created by AI and stimulate innovative development. The findings can be used to improve legislation at the national and international levels.